El Impacto de la Implementación de las Vías 4G en el Comercio Internacional de la Región Caribe (2020)
This monograph is focused in the need to know about the development of 4G roads over time since its implementation, in order to take the execution of these as an important factor in the Caribbean region considering itself an influential Region in the evolution of international trade in Colombian. In the first place it is widely expressed when, how and why previous generations of roads did not work in the way that different governments expected, the 4G roads project includes tunnels, bridges, dredging, and highways, which would facilitate the movement of commodity from the production sites to the different ports or airports, taking into account that the ports in the Colombian case they are far from large production centers.